2021
DOI: 10.3390/ijms22179333
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal-Freeze-Casting of Poly(amidoamine)-Modified Graphene Aerogels towards CO2 Adsorption

Abstract: This article presents novel poly(amidoamine) (PAMAM) dendrimer-modified with partially-reduced graphene oxide (rGO) aerogels, obtained using the combined solvothermal synthesis-freeze-casting approach. The properties of modified aerogels are investigated with varying synthesis conditions, such as dendrimer generation (G), GO:PAMAM wt. ratio, solvothermal temperature, and freeze-casting rate. Scanning electron microscopy, Fourier Transform Infrared spectroscopy, Raman spectroscopy, X-ray photoelectron spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 57 publications
6
6
0
Order By: Relevance
“…In accordance with Yao, S.Z. et al (2013) [30], as shown in Figure 2A, the peak at 1712 cm −1 was replaced with a new peak at 1163 cm −1 , representing C-N binding [31]. The amine group produced a peak at 667 cm −1 .…”
Section: Synthesis and Characterization Of Amine-functionalized Graphene Oxide (Afgo) And Amine-functionalized Graphene Oxide-doxorubicinsupporting
confidence: 86%
See 1 more Smart Citation
“…In accordance with Yao, S.Z. et al (2013) [30], as shown in Figure 2A, the peak at 1712 cm −1 was replaced with a new peak at 1163 cm −1 , representing C-N binding [31]. The amine group produced a peak at 667 cm −1 .…”
Section: Synthesis and Characterization Of Amine-functionalized Graphene Oxide (Afgo) And Amine-functionalized Graphene Oxide-doxorubicinsupporting
confidence: 86%
“…In accordance with Ya S.Z. et al (2013) [30], as shown in Figure 2A, the peak at 1712 cm −1 was replaced with new peak at 1163 cm −1 , representing C-N binding [31]. The amine group produced a pea Following the modification of GO, the structure of AFGO was analyzed using FTIR spectroscopy and EDS to confirm it was successfully prepared.…”
Section: Synthesis and Characterization Of Amine-functionalized Graphene Oxide (Afgo) And Amine-functionalized Graphene Oxide-doxorubicinsupporting
confidence: 71%
“…The density evolution for the aerogels modified with PAMAM and CNTs is depicted in Figure 1 B. The density ranged between 2.5 and 7 mg cm −3 , in agreement with similar aerogels [ 18 ]. Adding PAMAM molecules resulted in an increase in the modified aerogel density, reaching a maximum of 7 mg cm −3 for the higher content of PAMAM, which was attributed to the higher degree of functionalization.…”
Section: Resultssupporting
confidence: 71%
“…Recently, poly(amidoamine) (PAMAM) dendrimers have gained research interest for CO 2 capture as they exhibit the advantage of a higher number of functional amine end groups that are available for cross-linking [ 15 , 16 , 17 ]. However, amongst the works on dendrimer-modified CO 2 sorbents, only a few deal with modified GO aerogels [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation